Economic Development and Female Labor Participation in the Middle East and North Africa : A Test of the U-Shape Hypothesis - Verme, Paolo (World Bank, Washington, DC, 2014)
The Middle East and North Africa region is known for having low female labor market participation rates as compared with its level of economic development. A possible explanation is that these countries find themselves at the turning point of the U-shape hypothesis when countries transition from declining to rising female participation rates. This paper tests the U-shape hypothesis in countries in the Middle East and North Africa. It finds that the region has outperformed other world regions in terms of the main drivers of the U-shape hypothesis, including gross domestic product per capita, economic transformation away from the agricultural sector, female education, and fertility rates. These facts are consistent with nonparametric evidence that shows countries in the region are distributed over a U-shaped curve. However, parametric tests of the hypothesis point in a different direction. The region shows an inverted U-shape overall and great heterogeneity across countries and age cohorts that defies any law on the relation between gross domestic product and female participation rate. The explanation behind these findings may be economic and cultural. Jobless growth and the lack of growth in employment sectors such as manufacturing and services, which proved critical for female employment in other countries, weaken labor demand and strengthen the role of institutions that may discourage female participation, such as marriage, legislation, and gender norms.